(untitled) (American Journal of Islam and Society, 1991)
The Polemics of Ijtihad From the second hijri century until the present day, the reality, the essence, the rules, the conditions, the premises, the means, and the scope of ijtihad have remained a source of debate engaging some of the Islamic world’s greatest theologians, scholars of al usul, and fuqaha’: This debate has also been enriched by proponents of the view that the door of ijtihad was closed and that the fiqh left by the Four Imams obviated the need for any further ijtihad, as well as by those who claimed that this door was still open and that the existing fiqh was not sufficient to guide the contemporary Muslim world. In our own times, attention is now focused on the suitability of the Shari’ah as an order and a way of life. This new topic of debate, before unknown among Muslims, emerged after the crushmg defeats experienced by the Muslim ummah after the First World War, such as the dismantling of the khihfah and the creation of artificial states ruled from Europe. Many Muslims blamed Islam and its institutions for their defeat, and soon began to emulate their conquerors. Others, however, had a quite different view: the Muslim ummah experienced these disasters because it had become alienated from the eternal truths of Islam. Thus, what was required was a return to the true Islam and not its wholesale rejection in favor of alien institutions and ideologies. One fundamental part of this return would have to be the use of ijtihad, for how else could Muslims incorporate Islamic principles into situations with which they had never had to deal? Muslims who hold the latter view are aware of the fact that they must meet their opponents in the realm of ideas, for it is here that the future course of the ummah will be decided. To be successful, much energy must be expended in scholarship and conceptual thinking, in seeking to understand humanity’s place in the divine scheme of existence and what is expected of it, and how this knowledge might be applied by Muslims as they struggle ...